(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Determination of in-situ stress serves as an important step in the design and construction of civil and mining projects, among others. Conventional methods of the in-situ stress measurement are time- and cost-intensive. Therefore, application of low-cost yet rapid methodologies for in-situ stress evaluation has been increasingly regarded by researchers. The Kaiser Effect-based acoustic emission method is one of such novel approaches to the in-situ stress evaluation. Not only the point at which the Kaiser Effect occurs, but also the mechanism of the Kaiser Effect is of paramount importance. In this research, acoustic emission tests were conducted on phyllite rock samples under Brazilian tensile loading to collect a variety of acoustic data including the amplitude, rise time, count, duration, and energy. Then, the Kaiser Effect point was determined using the collected data on acoustic parameters, with its occurrence mechanism investigated. In addition, mathematical transformations were adopted to transform the acoustic signal from the time domain to the frequency domain, where the peak frequency was analyzed. Results of RA/AF ratio analysis showed that the acoustic emission was sourced from tensile micro-cracks. Moreover, the high level of energy indicated a high intensity of crack formation at the Kaiser Effect point. The large number of received hits showed that the count of generated cracks increases abruptly within the range of Kaiser Effect. In addition, the obtained high value of the peak frequency implied that the crack growth rate is high at the Kaiser Effect point.